Author Correction: Non-flammable electrolyte enables Li-metal batteries with aggressive cathode chemistries. Issue 12 (December 2018) - Fan, Xiulin; Chen, Long; Borodin, Oleg; Ji, Xiao; Chen, Ji; Hou, Singyuk; Deng, Tao; Zheng, Jing; Yang, Chongyin; Liou, Sz-Chian; Amine, Khalil; Xu, Kang; et al.
In the version of this Article originally published, in the first paragraph of the Methods, HFE was incorrectly given as 2, 2, 2-Trifluoroethyl-3ʹ, 3ʹ, 3ʹ, 2ʹ, 2ʹ-pentafluoropropyl ether; it should have been 1, 1, 2, 2-tetrafluoroethyl-2ʹ, 2ʹ, 2ʹ-trifluoroethyl ether. This has now been corrected in the online versions of the Article.